2019
DOI: 10.1590/1807-3107bor-2019.vol33.0110
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review and meta-analysis of welding procedures in one-piece cast implant-supported frameworks

Abstract: The objective of this systematic review and meta-analysis was to evaluate the effect of welding techniques on implant-supported prostheses and determine whether they contribute to a better adaptation compared with a one-piece cast. A search was conducted using the PubMed/MEDLINE, Embase, and Cochrane Library databases, and articles published until November 2017 were obtained from these databases. This review followed the PRISMA criteria and is registered on the PROSPERO platform (CRD42017081865). The PICO ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
0
1
0
Order By: Relevance
“…Furthermore, this technique yields a framework with reasonable hardness and minimizes the heat-affected zone, which is crucial for maintaining the integrity of the material. 32 De Castro et al evaluated stress distribution in Co-Cr frameworks with the use of laser welding and TIG welding, and concluded that the stress generated around the implants was similar for both techniques. 25 In the present study, although laser welding presented high stress between the implants, TIG welding showed the highest shear stress values in the crestal bone region at 3 key points, as well as in the apical region of the implants for both the EH and MT connections.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this technique yields a framework with reasonable hardness and minimizes the heat-affected zone, which is crucial for maintaining the integrity of the material. 32 De Castro et al evaluated stress distribution in Co-Cr frameworks with the use of laser welding and TIG welding, and concluded that the stress generated around the implants was similar for both techniques. 25 In the present study, although laser welding presented high stress between the implants, TIG welding showed the highest shear stress values in the crestal bone region at 3 key points, as well as in the apical region of the implants for both the EH and MT connections.…”
Section: Discussionmentioning
confidence: 99%